Despite benefits, commercialization of transgenic horticultural crops lags - Clark, David (CALIFORNIA AGRICULTURE, 2018)
The acreage of agronomic crops (soybean, cotton, corn and canola) developed using recombinant DNA technology has expanded dramatically since their introduction in 1996, while the commercialization of biotech horticultural crops (vegetables, fruits, nuts and ornamentals) has languished. This is not due to a lack of both current and potential traits that could be utilized in horticultural crops, as ongoing research is identifying a diverse array of applications. However, commercialization is stalled by market reluctance to accept biotech products, particularly in the absence of clear benefits to consumers. High regulatory costs and restricted access to intellectual property create additional hurdles for specialty crops. These challenges are causing the horticultural industry to forego a number of current benefits. New products with clear advantages for producers, marketers and consumers may be required before the potential of biotechnology can be realized.